1990
DOI: 10.7326/0003-4819-113-5-352
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Renal Crisis in Systemic Sclerosis: Relation to Availability of Angiotensin Converting Enzyme (ACE) Inhibitors

Abstract: Patients with systemic sclerosis who develop hypertension should be treated with an ACE inhibitor. Improved survival and successful discontinuation of dialysis are possible when ACE inhibitors are used to treat scleroderma renal crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
187
1
16

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 387 publications
(210 citation statements)
references
References 22 publications
6
187
1
16
Order By: Relevance
“…Although limited, this RCT methodology represents the best we have been able to accomplish at this time. Furthermore, the data from this protocol population are remarkably consistent with those from previously published longitudinal observational studies in patients with recent-onset diffuse disease (2)(3)(4)(5). This RCT failed to document efficacy of an accepted therapy, yet few, if any, previous RCTs in SSc have included such a large number of patients.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Although limited, this RCT methodology represents the best we have been able to accomplish at this time. Furthermore, the data from this protocol population are remarkably consistent with those from previously published longitudinal observational studies in patients with recent-onset diffuse disease (2)(3)(4)(5). This RCT failed to document efficacy of an accepted therapy, yet few, if any, previous RCTs in SSc have included such a large number of patients.…”
supporting
confidence: 81%
“…More importantly, 9 patients (50%) with renal crisis died during the relatively brief followup period of 4.0 Ϯ 1.1 years, within 0.9 Ϯ 1.1 years after the onset of symptoms consistent with renal crisis. This is an important point to emphasize in view of the high regard for angiotensin-converting enzyme (ACE) inhibitor therapy (3).…”
mentioning
confidence: 99%
“…Since 1984, Steen et al have reported their experience with SSc renal disease, derived from an observational study in which a large group of SSc patients were followed up prospectively since 1972 (2)(3)(4). They reported that 1-year survival in SRC patients treated with ACE inhibitors was 76%, compared with 18% in SRC patients not treated with ACE inhibitors, and that 5-year survival in SRC patients treated with ACE inhibitors was 60%.…”
mentioning
confidence: 99%
“…Risk factors that Steen et al and other investigators have identified as being predictive of SRC include new anemia, new cardiac events (e.g., pericardial effusion or congestive heart failure), use of prednisone in dosages Ͼ15-20 mg/day, diffuse skin thickening, rapidly progressive skin thickening, SSc disease duration Ͻ4 years, and the presence of anti-RNA polymerase III antibody (1)(2)(3)(4)(5). Urinary abnormalities and elevations of serum creatinine or plasma renin preceding the onset of SRC have not been shown to predict SRC.…”
mentioning
confidence: 99%
“…They offer greater than four-fold 1-year survival compared to non-treated patients and result in notably decreased SRC-related mortality [49]. However, no controlled clinical trial has yet been conducted [41].…”
Section: Interstitial Lung Diseasementioning
confidence: 99%